2014
DOI: 10.1111/hiv.12195
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in cytochrome P450 3A4 activity as measured by a urine cortisol assay in HIV‐1‐infected pregnant women and relationship to antiretroviral pharmacokinetics

Abstract: Objectives Pregnancy results in physiological changes altering the pharmacokinetics of drugs metabolized by cytochrome p450 3A4. The urinary ratio of 6-β hydroxycortisol to cortisol (6βHF:F) is a marker of CYP3A4 induction. We sought to evaluate its change in antiretroviral (ARV) treated HIV-1-infected women and to relate this change to ARV pharmacokinetics. Methods Women receiving various ARV had pharmacokinetic evaluations during third trimester pregnancy (>30 weeks) and postpartum with determination of 6β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The results of our population pharmacokinetic analysis estimated LPV clearance postpartum to be 26.4% and 37.1% lower than the clearance in nonpregnant subjects and pregnant women, respectively. A recent study estimated a similar magnitude of higher CYP3A4 activity in pregnant women (35%) than in postpartum subjects as measured by the urinary ratio of 6-␤-hydroxycortisol to cortisol as a marker (34). Several other studies investigating the pharmacokinetics of LPV/r tablets in pregnant women similarly reported LPV exposure during the third trimester with the 400/100-mg BID tablet dose to be 35% to 45% lower than the postpartum exposure (18,(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 85%
“…The results of our population pharmacokinetic analysis estimated LPV clearance postpartum to be 26.4% and 37.1% lower than the clearance in nonpregnant subjects and pregnant women, respectively. A recent study estimated a similar magnitude of higher CYP3A4 activity in pregnant women (35%) than in postpartum subjects as measured by the urinary ratio of 6-␤-hydroxycortisol to cortisol as a marker (34). Several other studies investigating the pharmacokinetics of LPV/r tablets in pregnant women similarly reported LPV exposure during the third trimester with the 400/100-mg BID tablet dose to be 35% to 45% lower than the postpartum exposure (18,(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 85%
“…The model indicated that gestational age has a more profound effect on the elimination of RTV than LPV, implying that RTV is more sensitive to physiologic changes, including the potential alteration of metabolic enzyme activity. 30 The increase in CL u,LPV /F is 38%, 56%, and 61% at 22 weeks, 30 weeks, and 32 weeks, respectively, of gestation compared to postpartum in terms of the median post hoc PK estimates. Decreases in the drug bioavailability, increase in metabolic enzyme activity, or both could explain this increase; however, our model could not quantitatively differentiate the effect of these two factors due to lack of i.v.-administration PK or a direct assessment of metabolic activity.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, this is the first model to use an exponential function to describe the longitudinal change of the apparent intrinsic clearance for LPV and RTV in pregnant women. The model indicated that gestational age has a more profound effect on the elimination of RTV than LPV, implying that RTV is more sensitive to physiologic changes, including the potential alteration of metabolic enzyme activity . The increase in CL u,LPV /F is 38%, 56%, and 61% at 22 weeks, 30 weeks, and 32 weeks, respectively, of gestation compared to postpartum in terms of the median post hoc PK estimates.…”
Section: Discussionmentioning
confidence: 97%
“…As previously stated, elvitegravir is primarily metabolized by CYP3A4 [ 52 ], and its pharmacokinetics are boosted with cobicistat, a strong CYP3A4 inhibitor, to assure adequate exposure. During pregnancy, induction of CYP3A4 is expected, based on in vitro [ 20 ] and in vivo data [ 21 , 22 ]. This induction may therefore also affect the pharmacokinetics of elvitegravir, and can be explained by two mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Serum protein concentrations may change during pregnancy, which may have consequences for the protein unbound (free) fraction of drugs [ 15 ]. Lastly, increased hormone levels during pregnancy may change the expression of metabolizing enzymes, such as UDP-glucuronosyltransferase 1A1 (UGT1A1) [ 16 18 ] and cytochrome P450 (CYP) 3A4 [ 19 22 ]. Induction of these isoenzymes may lead to increased apparent clearance (CL/F) and hence a change in exposure to HIV-integrase inhibitors.…”
Section: Introductionmentioning
confidence: 99%